2018
DOI: 10.1016/j.jclepro.2017.11.198
|View full text |Cite
|
Sign up to set email alerts
|

Performance assessment and life cycle analysis of potable water production from harvested rainwater by a decentralized system

Abstract: a b s t r a c tDecentralized rainwater harvesting (RWH) from roof runoff can complement the centralized supply of mains (drinking) water for a range of contexts, to assist in alleviating issues of water security. However, treatment to potable standard of harvested rainwater is not widespread. Consequently a comparative life cycle analysis (LCA) of decentralized and centralized potable water supply has not previously been undertaken. In this paper we describe a novel point-of-use (POU) treatment device, which w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 17 publications
0
25
0
Order By: Relevance
“…The authors further confirmed their findings' compliance with the national (German) requirements for treated effluent reuse. In another study, Yan et al (2018) set up a rainwater harvesting system in an office building on the University of Exeter's Streatham campus with around 300 occupants. Although the rainwater harvesting system aimed to reduce water consumption in the toilet flushing, the system enabled to get water with a quality met with the criteria for the potable water in the UK which can also be used for washing the building and drinking.…”
Section: Technology Readiness Levels Of Solutions To Close Water Loopsmentioning
confidence: 99%
“…The authors further confirmed their findings' compliance with the national (German) requirements for treated effluent reuse. In another study, Yan et al (2018) set up a rainwater harvesting system in an office building on the University of Exeter's Streatham campus with around 300 occupants. Although the rainwater harvesting system aimed to reduce water consumption in the toilet flushing, the system enabled to get water with a quality met with the criteria for the potable water in the UK which can also be used for washing the building and drinking.…”
Section: Technology Readiness Levels Of Solutions To Close Water Loopsmentioning
confidence: 99%
“…Recently this has changed and perhaps the most well known and applied addition to represent environmental aspects within urban water infrastructure engineering assessment currently is life-cycle assessment or analysis (LCA) or life-cycle impact assessment (as according to ISO 14040:2006 and14044:2006). Traditionally used to assess environmental impacts associated with product design, manufacture and decommissioning, LCA has more recently been applied to wastewater, drinking water, stormwater and integrated urban water systems (Byrne et al 2017) and to compare decentralised and centralised water systems for potable water production from harvested rainwater (Yan et al 2017).…”
Section: The Present: Greening Engineering Assessmentmentioning
confidence: 99%
“…The present water scarcity leads to a new paradigm in water resource management, and the application of sustainable water supply solutions is essential [6,7]. Some studies [8,9] have catalyzed interest in alternative approaches to ensure water security by applying, for example, rainwater harvesting systems.…”
Section: Introductionmentioning
confidence: 99%